Unusual Periodontal Lesion of the Permanent Upper Central Incisor Induced by the Implantation of a Foreign Materiál (Localized Periodontal Destruction) - R. Slezák; V. Radochová; M. Šembera (Czech Dental Chamber, 2018)
Introduction, aim: Case report deals with the observation of a less common isolated periodontal damage of a permanent tooth in a young female, the cause of which was an unwanted and unconscious self-implantation of hair particles into the gingival sulcus of the permanent upper central incisor. Methods: Retrospective evaluation of the case report. Results: Causal therapy led to the rapid healing of the periodontal defect and preservation of her own tooth. Conclusion: The necessity of a regular and complex evaluation of every young individual with serious damage of the periodontal tissue including detailed history of the patient that could be rather difficult, was discussed. Correct diagnosis is a prerequisite for the adequate and successful treatment of all less common periodontal diseases.